Conflicted Power in Malawian Christianity : Essays Missionary and Evangelical from Malawi - Fiedler, K. (Klaus), 1942- (Book collections on Project MUSE., 2015)
The volume constitutes Klaus Fiedler's crowning contribution to scholarship. Essays in the first half of the book focus on Malawian Christianity and how contrasting Powers, Gospel and Secular, engage each other, creating social, political and cultural conflict in the process. In the second half, Fiedler examines general missiological themes. These essays provide a broader missiological background, offering a theoretical framework necessary for appreciating the essays in the first half. He concludes with a chapter that reviews selected seminal books on themes under study. Throughout the volume Fiedler applies the "restorationist revival theory" he constructed in The Story of Faith Missions, an earlier 1994 work putting emphasis on non classical missions and churches, not systematically covered in earlier scholarship. This volume, the first of its kind on Malawian Christianity, will long remain an indispensable text for those interested in Missiology and Malawian Christianity.